RNA 2’-O-Methyltransferase Fibrillarin Facilitates Virus Entry Into Macrophages Through Inhibiting Type I Interferon Response - Li, Panpan; Liu, Yang; Song, Renjie; Zhao, Lu; Yang, Jiang; Lu, Fengjiao; Cao, Xuetao (Frontiers in Immunology, 2022)
Type I interferons (IFN-I) play crucial roles in antiviral immune responses through inducing multiple antiviral interferon stimulated genes (ISGs). RNA modifications are emerging as critical post-transcriptional regulators of gene expression programs, which affect diverse biological processes. 2'-O-methylation (Nm) is one of the most common types of RNA modifications found in several kinds of RNA. However, the function and underlying mechanism of Nm modification in regulating viral infection and innate immunity are largely unknown. Here we found that 2'-O-methyladenosine (Am) on poly A+ RNA was increased in virus infected-macrophages. Functional screening identified RNA 2'-O-methyltransferase Fibrillarin (FBL) in facilitating viral infection. Down-regulation of FBL inhibited viral infection through blocking virus entry into macrophages. Furthermore, knockdown of FBL could reduce viral entry by increasing ISGs expression through IFN-I signaling. These results indicated that FBL-mediated Nm modifications of RNA may avoid the innate immune recognition, thereby maintain immune homeostasis. Once FBL is down-regulated, the decreased Nm modifications of RNA in macrophages may act as “non-self” RNA and be recognized by RNA sensor interferon induced with helicase C domain 1 (MDA5), leading to innate immune activation by inducing the expression of IFN-I and ISGs. Therefore, our finding reveals a new role of FBL and its mediated RNA Nm modifications in facilitating viral infection and inhibiting innate immune response, adding mechanistic insight to the RNA modifications in infection and immunity.